AWARD ACCEPTANCE SPEECHES: LINGUOSTYLISTIC FEATURES: - Harutyunyan, Kristine (Armenian Folia Anglistika, 2022)
The present paper investigates linguostylistic features peculiar to celebrities’ award receiving speeches - a public discourse variety of modern English which is popular not only for its social importance but also for its linguistic and stylistic significance. The results of the analyses carried out on the basis of linguostylistic and case study methodology show that emotional colouring and expressiveness are the most typical characteristics of award acceptance speeches. The impact on the listener or reader is achieved through the usage of different literary-stylistic devices. The award receiving speeches also make a strong emotional impact on the listener during celebrations and through them, while the length (conciseness or wordiness) does not minimize the strong influence on the audience.